Effectiveness of Intergovernmental Grants: A Systematic Literature Review - Fitriadi, Fitriadi; Haliah, Haliah; Nirwana, Nirwana; Kusumawati, Andi (Economics, Business, Accounting & Society Review, 2024)
This article aims to analyze the effectiveness of intergovernmental grants. Although the government has provided grants to various entities, including intergovernmental ones, there has yet to be a comprehensive study that illustrates the effectiveness of these intergovernmental grants. Systematic Literature Review and meta-analysis are used to answer the research question. There are 199 articles found using the keyword "government grants" from 1902 to 2023, which were then filtered based on the article year from 2010 to 2023, articles published in reputable journals indexed in Scopus Q1 to Q4, and several other limitations, resulting in 14 articles that became the data for analysis in this study. Research results show that intergovernmental grants are very effective for regions with budget and resource limitations to support development programs, enhance fiscal capacity and infrastructure, and meet the community's social needs with the hope of increasing development equity and reducing economic disparities. However, the effectiveness of intergovernmental grants depends on how these are managed and used. If not handled properly, grants can become a source of waste and public dissatisfaction, as they may be used for political purposes. In contrast, some local governments tend to use grants for electoral or short-term interests, which can disrupt their fiscal independence. Therefore, creating a balance between grants and local revenue is important. This research contributes by exploring the role, impact, and challenges of intergovernmental grants in supporting regional development in a decentralized government system.